2019
DOI: 10.1088/1361-651x/ab2621
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and grain size dependences of mechanical properties of nanocrystalline copper by molecular dynamics simulation

Abstract: Nanocrystalline copper (Cu) is considered to be one of the best interconnected material in integration circuit (IC) industry, because of its ultra-low resistivity and high mechanical stability. Mechanical properties of nanocrystalline Cu are completely different from those of bulk monocrystalline Cu. These properties are of high importance in the assessment of the thermo-mechanical reliability of the interconnected IC structure. To investigate the effects of the grain sizes and temperature on the mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…The results showed that the stress-dominated deformation mechanism at grain boundaries is insensitive to strain rate, while stacking faults impede the movement of some dislocations, which leads to an increase in strain rate sensitivity. Chen et al [9] investigated the effect of strain rate on the mechanical properties of polyCu. The simulated results showed that the mechanical properties of polyCu were sensitive to high strain rates (1 × 10 9 s −1 ∼5 × 10 10 s −1 ), but the properties did not change much at low strain rates (5 × 10 7 s −1 ∼1 × 10 9 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the stress-dominated deformation mechanism at grain boundaries is insensitive to strain rate, while stacking faults impede the movement of some dislocations, which leads to an increase in strain rate sensitivity. Chen et al [9] investigated the effect of strain rate on the mechanical properties of polyCu. The simulated results showed that the mechanical properties of polyCu were sensitive to high strain rates (1 × 10 9 s −1 ∼5 × 10 10 s −1 ), but the properties did not change much at low strain rates (5 × 10 7 s −1 ∼1 × 10 9 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, the elastic modulus decreases with increasing temperature, which indicates an increase in the diffusion capacity of the atoms under external loading due to the thermally-reduced bond energy. 55,56 The higher the temperature, the lower the deformation resistance of the atom, which is manifested by a low elastic modulus. Furthermore, the slope of the elastic modulus–temperature curve is similar for NC-Ta with different average grain sizes, implying that the temperature dependence of the mechanical properties is not affected by the grain size.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Figures 4c and d that the grain boundaries are sliding from their original shape and shifting to newer formations. This mechanism is found to exist in previous studies as well (Li et al ., 2019; Jeon et al ., 2010; Chen et al ., 2019; Zhang et al ., 2020). This sliding of grain boundaries can be seen in Figures 4a and b where grain boundary between grain numbers 1 and 4 is found developing in the encircled region.…”
Section: Resultsmentioning
confidence: 99%